HDPE Bag Production Waste Fell After Integrated Lean Analysis - Gairwyn, Shannon Viona; SZS, Joumil Aidil (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Production efficiency is essential for manufacturing competitiveness, yet many systems remain dominated by non value added activities and seven waste categories. Specific Background: In HDPE plastic bag production, a defect rate of 7.02% exceeds the 3% standard and is accompanied by waiting, motion, and process inefficiencies. Knowledge Gap: Limited studies integrate Lean Manufacturing with Failure Mode and Effect Analysis in HDPE bag production contexts. Aims: This study aims to identify dominant waste and formulate improvement strategies using an integrated Lean approach. Results: Seven waste types were identified, with defects (RPN 441) and waiting (RPN 336) as priorities; improvements reduced activities from 39 to 31, decreased lead time from 214.94 to 151.14 minutes, and increased process cycle efficiency from 45.42% to 64.59%. Novelty: This study integrates Value Stream Mapping, Process Activity Mapping, fishbone diagram, and FMEA within a single framework tailored to HDPE bag production. Implications: The findings demonstrate that systematic waste identification and elimination of non value added activities improve production flow, quality, and operational efficiency while supporting structured maintenance and pull-based systems. Highlights: Defect and waiting categories ranked as highest priority based on risk evaluation. Process restructuring reduced total operational steps and shortened processing duration. Integrated mapping and risk assessment enabled systematic identification of root causes. Keywords: Lean Manufacturing, FMEA, HDPE Plastic Bags, Waste, Production Process.